Incidence and tumour characteristics of bilateral and unilateral interval breast cancers at screening mammography. (April 2018) - van Bommel, Rob M.G.; Voogd, Adri C.; Nederend, Joost; Setz-Pels, Wikke; Louwman, Marieke W.J.; Strobbe, Luc J.; Venderink, Dick; Tjan-Heijnen, Vivianne C.G.; Duijm, Lucien E.M.
Abstract: Background: Detected by screening mammography, bilateral breast cancer has a different pathological profile compared to unilateral breast cancer. We investigated the incidence of bilateral interval breast cancers and compared their characteristics with those of unilateral interval breast cancers. Methods: We included all 468, 720 screening mammograms of women who underwent biennial screening mammography in the South of the Netherlands between January 2005 and January 2015. We collected breast imaging reports, biopsy results and surgical reports of all referred women and of all women who presented with interval breast cancer. The tumour with the highest tumour stage (index cancer) was used for comparison with unilateral interval cancers. Results: A total of 753 interval cancers were detected, of which 24 (3.2%) were bilateral. Among the invasive interval cancers, bilateral cancers more frequently showed a lobular histology than unilateral cancers (37.5% (9/24) vs. 16.1% (111/691), P = .01). There is a trend towards a larger proportion of bilateral than unilateral interval cancers graded 1 (45.8% (11/24) vs. 27.8% (192/691), P = .08). There were no other statistically significant differences in tumour characteristics. Also, the proportion of interval cancers showing significant mammographic abnormalities at the latest screen was comparable for unilateral and bilateral interval cancers (23.0% vs. 25.0%, P = .9). Discussion: Bilateral interval cancers comprise a small proportion of all interval cancers. Except of a higher proportion of invasive lobular cancers and a more favourable histological grade of invasive cancers, tumour characteristics are comparable for bilateral and unilateral interval breast cancers. Highlights: Synchronous bilateral interval cancer comprises 3.2% of all interval cancers. Bilateral interval cancer are more likely to show invasive lobular histology. Bilateral interval cancer has a more favourable histological grade compared to unilateral interval cancer. Other tumour characteristics are comparable between unilateral and bilateral interval cancer.